Social Relations and Interpersonal Dialogue among Couples: A Study in the City of Yazd Based on the Grounded Theory - Lida Hatefi rad; Mehraban Parsamehr; Ali Ruhani (Strategic Research on Social Problems)
Introduction The family as the most significant and fundamental social institution exerts direct and profound influences on other societal institutions. It assumes distinct roles and functions and addresses a range of human needs. Central to family life and functioning are the relationships among family members. Communication serves as the foundation through which families define themselves and members acquire the skills to navigate shared meanings (Miller, 2017). Consequently, communication and interactions between family members emerge as crucial characteristics within any family unit. When communication is positive and effective, it ensures the overall well-being of the family and, in turn, contributes to the health of society as a whole. Effective communication skills encompass both verbal and nonverbal elements with effective verbal and conversational skills occupying a significant role in marital communication. Furthermore, communication within the family, like any other form of dialogue, is influenced by cultural and social contexts. Dialogue, in fact, not only stems from an individual's background and social network, but also shapes the formation of future relationships and interactions. As per Michel's definition, a social network comprises unique connections among a specific group of individuals. These connections collectively provide insights into the social behavior exhibited by the individuals involved (Mitchel, 1999). Therefore, recognizing the pivotal role played by tradition, culture, and social backgrounds in fostering interactions and dialogues between couples, this research aimed to comprehend the process of dialogue formation within the context of couples' social relations.